2016
DOI: 10.1177/2156587216631903
|View full text |Cite
|
Sign up to set email alerts
|

The Feasibility and Effectiveness of Online Guided Imagery Training for Health Professionals

Abstract: This study evaluated the feasibility and impact of brief online guided imagery training (up to 3 hours) for health professionals. Paired t tests were used to measure pre-to-post-training changes in stress (Perceived Stress Scale,), anxiety (Patient Reported Outcomes Measurement Information System-Anxiety Scale), empathy (Empathic Concern Scale, and Perspective-taking Scale), and self-efficacy (Self-Efficacy in providing Non-Drug Therapies Scale). Online guided imagery training attracted diverse health professi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
31
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 23 publications
(33 citation statements)
references
References 40 publications
2
31
0
Order By: Relevance
“…denial, frustration, guilt, etc., and develop their empathy skill directly. Despite a limited number of studies on the effect of GI on empathy level of the nurses, the existing ones are similar to the results of the present study [19,20]. These results suggested that GI would enhance the quality of care by decreasing the difficulty in developing empathy experienced by oncology nurses due to their death anxiety while providing care to terminally ill patients.…”
Section: Discussionsupporting
confidence: 88%
See 2 more Smart Citations
“…denial, frustration, guilt, etc., and develop their empathy skill directly. Despite a limited number of studies on the effect of GI on empathy level of the nurses, the existing ones are similar to the results of the present study [19,20]. These results suggested that GI would enhance the quality of care by decreasing the difficulty in developing empathy experienced by oncology nurses due to their death anxiety while providing care to terminally ill patients.…”
Section: Discussionsupporting
confidence: 88%
“…Several studies conducted over the past decade have reported that GI reduces depression, anxiety, stress, pain, and the chemotherapyinduced side effects, strengthens the immune system, and lowers high blood pressure [5][6][7][8][9][10][11][12][13][14][15][16]. A limited number of studies exist that examine the effect of GI on nursing practices [12,[17][18][19][20]. Studies on the use of GI in nursing care largely have investigated mostly the issues such as pain, stress, and fatigue management [12,[17][18][19][20].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“… 11 , 12 , 41 In fact, these earlier observations led us to evaluate a practical intervention aimed at improving mindfulness and resilience, online mind-body skills training, which our subsequent work suggested can lead to short-term improvements in stress and confidence in providing compassionate care in health care students, residents, and practicing clinicians. 16 19 This has important implications for patient care since more mindful clinicians provide more patient-centered care; Dobkin et al 42 showed that mindfulness training improved clinician’s mindfulness and well-being, and that patients perceived that more mindful clinicians provided more patient-centered care.…”
Section: Discussionmentioning
confidence: 99%
“…Rao and Kemper 46) delivered an online guided imagery intervention to a sample of 273 health professionals. The intervention, which comprised three modules of autogenic training and guided imagery, produced significant improvements in participants' reported levels of perceived stress, anxiety, empathy, and self-efficacy postintervention.…”
Section: Resultsmentioning
confidence: 99%